Species-specific identification of and distinction between Borrelia burgdorferi genomic groups by using 16S rRNA-directed oligonucleotide probes. - Marconi, R T (1992)
Examination of a number of previously published aligned Borrelia 16S rRNA sequences revealed the presence of regions which could serve as oligonucleotide probe targets for both species-specific identification of Borrelia burgdorferi and distinction between genomic groups. Total cellular RNA isolated from Borrelia cultures was used in slot blot analysis. Radiolabeled oligonucleotides designed to hybridize to specific 16S rRNA targets were used as probes. These probes allowed for both species-specific identification and genomic group typing of B. burgdorferi.